Nanotechnology in textiles : theory and application - Mishra, Rajesh; Militky, Jiri (Textile Institute book series., 2019)
Nanotechnology in Textiles: Theory and Application explains how conventional methods for treating fabrics for specific functions can by improved upon with the use of nanotechnology. Overviews of relevant, fundamental nanophysics and nanochemistry theory are provided, along with explanations of their application in textile finishing, providing a crucial resource for readers exploring this expanding frontier in textiles. The book draws on research from around the globe to address the latest nanotechnological developments that are all examined with references to industrial applications.